Is there a potential of emission of sequestered CO2 from Illinois bituminous coal under shockwaves?. (15th June 2015) - Harbin, Samuel; Twombly, Nickolas J.; West, Richard D.; Malhotra, Vivak M.
Highlights: Probed how shockwaves may affect the sequestered CO2 in bituminous coal. Fabricated a system to apply shockwaves to cores while monitoring emitted gases. Shockwaves did not induce gas emission from non-pressurized coal cores. Massive amounts of CO2 emitted from coal cores under compressive shock. Shocks ejected almost all the CO2 from pressurized coal in less than 1 h. Abstract: The mitigation of potential global warming due to the emission of greenhouse gases, especially CO2, would require large-scale geological sequestration. Though current emphasis has been on identifying and characterizing the potential geological sequestration reservoirs, there is also an urgent need to ensure that the sequestered CO2 will remain in place under reasonable perturbations, e.g., under seismic activity. One of the potential geological reservoirs identified is unmineable coal seams due to the advantage of recovering fuel gas like CH4 while sequestering CO2 . Therefore, a closed experimental setup was constructed where Illinois bituminous coal cores could be subjected to compressive shockwaves while simultaneously monitoring the emission of gases from CO2 pressurized coal cores. The results from the pressurized coal cores were compared with the behavior manifested by un-pressurized coal cores as well as porous pumice stone cores, which were also subjected to shockwaves. As expected, the un-pressurized cores showed no significant emission of CO2 when subjected to shock; however, this was not the case for the cores which were pressurized with CO2 . The results indicate that massive amounts of CO2 would be emitted if the cores were exposed to atmospheric pressure simulating a situation where caprock has been compromised during primary seismic activity. Irrespective of the belief that coal interacts strongly with CO2, both chemically and physically, compressive (0.374 MPa) shockwaves forced almost all the CO2 to be ejected from the coal cores. Surprisingly, most, if not all, the sequestered CO2 would be emitted in less than 1 h if the cores were subjected to reasonably moderate shocks. In actual seismic activity conditions, one expects conditions to be even more severe than in the experimental setup used in this study because of the presence of compressive and transverse stresses and shears. If such is the case, CO2 may be emitted even faster. It is reasonable to argue that Illinois bituminous coals may not be suitable hosts for sequestering CO2 because the region is prone to seismic activity.